(untitled) (Indonesian Theological Justice Review, 2024)
Indonesia’s religious diversity often serves as a source of strength, but it can also lead to interreligious conflict. This paper explores how theology, particularly interfaith dialogue and cooperation, can contribute to peacebuilding and social justice in Indonesia. Focusing on Islamic, Christian, Hindu, and indigenous religious perspectives, the study examines how these faiths interpret and promote peace, justice, and reconciliation. The paper reviews case studies of successful interfaith peacebuilding initiatives, including efforts to mediate conflict between religious groups, promote understanding, and build shared commitments to social justice. By analyzing religious teachings on forgiveness, the sanctity of life, and the common good, the research argues that interfaith theology can offer powerful tools for conflict resolution and social cohesion. The paper also addresses the challenges of interfaith dialogue, such as religious intolerance, political polarization, and sectarian violence. Recommendations include strengthening interfaith education, promoting collaborative peacebuilding projects, and encouraging religious leaders to use theological teachings to advocate for justice and reconciliation in conflict areas.